Implementation of Livable House Standards for Earthquake Resistance in Bandung Regency - Michael Sian Adrian Geoffrey Santoso; Anang Kristianto (Journal of Innovation and Community Engagement, 2023)
The BSPS (Bantuan Stimulan Perumahan Swadaya) program organized by the Directorate General of Housing of the Ministry of Public Works and Public Housing is a program implemented as a form of improving the quality of self-help housing. Although simple, building like this requires sufficient resistance to earthquakes. The results of the calculation of earthquake resistance that begins with loading the roof obtained a live load of 1.38 N, a super dead load of 0.75 N, and a dead load of 132102.5 N. Further testing on the calculation of ring beams results in ring beams being able to withstand a load of 1 .7191 kN with the help of the column interaction diagram states that the column is able to withstand a load of 252.6964 kN. The results of the ground spectrum response test show that Bandung district has a high earthquake risk and a class II risk period. Static power testing in the x and y directions is 270 kg and 260 kg. the level deviation on the x-axis is 0.0706500 mm and on the y-axis is 0.05575000 mm. This has proven the house to be resistant to earthquakes. Subsequent work can be in accordance with the standards given during the construction process. This building is resistant to earthquakes but the work requires more careful supervision.